Manajemen Perpustakaan dalam Upaya Peningkatan Kemampuan Literasi Peserta Didik di SMK Negeri 2 Panyabungan (International Forum of Researchers and Lecturers, 2025)
Library Management in Efforts to Improve Students’ Literacy Skills at SMK Negeri 2 Panyabungan, aims to examine library management, students’ literacy abilities, and the supporting and inhibiting factors in enhancing literacy. Using a descriptive qualitative method, data were collected from librarians, students, the principal, and teachers. The findings show that library management consists of planning (goal setting, forming a literacy team, and planning programs such as morning assemblies), implementation (reading before lessons and searching for additional materials in the library), and evaluation (monitoring library visits, book loans, and the book collection). Students' literacy skills are considered good, as demonstrated through morning assembly activities, reading before classes, and active participation. Supporting factors include well-organized book collections, adequate facilities, and collaboration between the school administration, teachers, and librarians. On the other hand, inhibiting factors include poorly managed library visitation schedules, limited technological facilities, and an insufficient number of computers compared to the number of students. The study concludes that effective library management plays a significant role in improving students’ literacy, although further support is needed to overcome existing challenges.